Fixed Point Results for Almost ZG-contraction via Simulation Functions in G-metric spaces - et. al, V SRINIVAS CHARY (International Journal of Control and Automation, 2019)
Abstract: In this article, we derive the notion of almost - contraction and give the fixed point theorems of almost - contraction using simulation functions in -metric spaces and also give an application to integral equations.